Altered Response to Neuroendocrine Challenge Linked to Indices of the Metabolic Syndrome in Healthy Adults - Tyrka, A. R.; Walters, O. C.; Price, L. H.; Anderson, G. M.; Carpenter, L. L. (Hormone and Metabolic Research, 2012)
Metabolic syndrome (MetS) is characterized by central obesity, hypertension, insulin resistance, and hypercholesterolemia. Hypothalamic-pituitary-adrenal (HPA) axis activity is frequently abnormal in MetS, and excessive cortisol exposure may be implicated in metabolic derangements. We investigated the hypothesis that cortisol and adrenocorticotropic hormone (ACTH) responses to a standardized neuroendocrine challenge test would be associated with indices of MetS in a community sample of healthy adults. Healthy adults, 125 men and 170 women, without significant medical problems or chronic medications were recruited from the community. Participants completed the dexamethasone/corticotropin-releasing hormone (Dex/CRH) test, and anthropometric measurements, blood pressure, glycosylated hemoglobin (HbA1c), and cholesterol were measured. Participants reported on their history of early life stress and recent stress, as well as mood and anxiety symptoms. Cortisol and ACTH responses to the Dex/CRH test were negatively associated with measures of central adiposity (p<0.001) and blood pressure (p<0.01), and positively associated with HDL cholesterol (p<0.01). These findings remained significant after controlling for body mass index (BMI). Measures of stress and anxiety and depressive symptoms were negatively correlated with cortisol and ACTH responses in the Dex/CRH test but were not related to MetS indices. That altered HPA axis function is linked to MetS components even in a healthy community sample suggests that these processes may be involved in the pathogenesis of MetS. Identification of premorbid risk processes might allow for detection and intervention prior to the development of disease.
Keywords: metabolic syndrome; HPA axis; cortisol; ACTH; corticotrophin-releasing hormone